Engagement as an inherent aspect of the learning process. (June 2016) - Boekaerts, Monique
Abstract: This commentary describes the contribution of each individual paper to our understanding of engagement, as well as evaluating whether together these papers achieve the editor's goal of developing an emerging consensus on the meaning and measurement of this construct. Individually these papers extend our understanding of specific aspects of engagement and contextual effects on engagement in important ways, but together have fallen short of the ambitious goal of bringing the different conceptualizations, measurements, and methods into closer alignment. The commentary concludes with a discussion of three issues that need to be addressed in future research on engagement including: 1) examining the degree of overlap between engagement and self-regulation, 2) more clearly articulating the role of affect in engagement, and 3) describing the crucial role of goals in engagement and learning. Highlights: Strengths and limitations of papers in advancing our understanding of student engagement are outlined. Together papers fall short of goal of integrating literature around definitions and measures of engagement. Areas of future research on student engagement are presented.